2019
DOI: 10.1109/tnsre.2019.2936739
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Encoding Scheme for Delivering Artificial Sensory Information via Direct Brain Stimulation

Abstract: Innovations for creating somatosensation via direct electrical stimulation of the brain will be required for the next generation of bi-directional cortical neuroprostheses. The current lack of tactile perception and proprioceptive input likely imposes a fundamental limit on speed and accuracy of brain-controlled prostheses or re-animated limbs. This study addresses the unique challenge of identifying a robust, high bandwidth sensory encoding scheme in a high-dimensional parameter space. Previous studies demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Our results on behavioral sensitivity to detection of sensation in rodents and primates were comparable to those observed with Intracortical Microstimulation (ICMS) of S1 (5,17). Notably, sensitivity to stimulus amplitude increased with increasing pulse width, frequency, and duration of stimulation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results on behavioral sensitivity to detection of sensation in rodents and primates were comparable to those observed with Intracortical Microstimulation (ICMS) of S1 (5,17). Notably, sensitivity to stimulus amplitude increased with increasing pulse width, frequency, and duration of stimulation.…”
Section: Discussionsupporting
confidence: 83%
“…Frequency modulation has been historically considered a promising method for providing sensory feedback with several studies showing that animals are capable of discriminating ICMS frequencies and that frequency modulation obeys Weber's law. (4,(20)(21)(22), While ICMS amplitude modulation in monkeys failed to follow Weber's law (5), experiments in rats showed that modulation of perceived intensity by amplitude and pulse-width modulation followed Weber's law (17). In our study, we investigated whether rats and monkeys could learn to discriminate SCS frequencies.…”
Section: Discussionmentioning
confidence: 96%
“…Intra-cortical micro-stimulation (ICMS) patterns were generated using four key parameters [59]: pulse amplitude, pulse-width, stimulation frequency and total stimulation duration (Figure 1C). Pulse-amplitude ranged from 1-100µA, pulse-width from 44-400µsec, while the stimulation frequency was fixed at 300Hz and duration lasted up to 1s.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested electrical charge as a powerful modulator of somatosensory sensations in single-channel ICMS [28], [59], [60]. Specific spatial patterns of charge, delivered over multiple ICMS channels, may be an important parameter for targeting specific percepts or somatotopic locations [34] [39].…”
Section: Spatial Patterns Of Icms Analyze Role Of Charge In Evoked So...mentioning
confidence: 99%
“…tingling, as reported by the users [2]- [4], [6]- [11]. However, different groups approach this problem from different angles with marked differences in the site in the nervous system where the stimulation is delivered: central [12]- [14] vs. peripheral nervous system [2], [15]- [17]; invasive [2], [7], [8], [10], [18] vs. non-invasive [5], [17], [19]; and the way the neural stimulation is modulated to convey sensory precepts: biomimetic [8]- [10], [20]- [23] vs. abstract [13], [17], [21], [24]. We believe that this diversity is due to three main reasons: 1. uncertainty on how to best sense and convert sensory information from the environment to electrical patterns to stimulate the nervous system and evoke naturalistic sensation; 2. lack of technologies for targeted delivery of this information to the nervous system; and 3. research still ongoing on the development of biocompatible neural interfaces that allow direct communication with the peripheral nervous system without causing physical damage and pain.…”
mentioning
confidence: 99%